Effects of a parenting sexual education program for immigrant parents: A cluster randomized trial. Issue 2 (February 2020) - Lee, Pei-I; Lai, Hsiang-Ru; Lin, Pi-Chu; Kuo, Shu-Yu; Lin, Yen-Kuang; Chen, Su-Ru; Lee, Pi-Hsia
Highlights: Practical booklets and boosters improve parental sex education self-efficacy. A booster session with multiple strategies meets the needs of immigrant parents. Health care professionals should be concerned about the sex education of immigrant parents. Abstract: Objectives: The aim was to assess the effects of a parental sex education program on knowledge, attitudes, self-efficacy, and practices among immigrant parents. Methods: A cluster randomized trial was conducted at immigrant activity centers in northern Taiwan. Recruited participants were randomly assigned to an experimental (four centers, n  = 86) or control (four centers, n  = 67) group. A practical booklet and a booster session were delivered. In total, 132 participants' knowledge, attitudes, self-efficacy, and practice of parenting sexual education were examined at the baseline and 6 weeks after the intervention. Results: After controlling for possible confounders, the posttest scores of self-efficacy of the experimental group were higher than those of the control group. The Johnson-Neyman procedure indicated that the intervention was effective for participants who had pretest knowledge, attitude, and practice scores of <14.62, <110.27, and <41.5, respectively. Conclusions: An intervention with both practical booklet and booster session can improve knowledge, attitudes, self-efficacy and practices of parental sex education among immigrant parents. Practice implications: In addition to practical booklets, health care professionals should provide booster sessions that meet the needs of immigrant parents to prevent sexual problems among children and adolescents at an early age.